1996
DOI: 10.1021/ja9621861
|View full text |Cite
|
Sign up to set email alerts
|

Low Symmetry in P(NR2)3 Skeletons and Related Fragments:  An Inherent Phenomenon

Abstract: A single-crystal X-ray diffraction study at 110 K and ab initio calculations up to the MP2/6-31G* level of theory showed that the ground state of P(NMe2)3 has C s symmetry, with two different coordination geometries at the nitrogen atoms (pyramidal and planar). The calculated and experimentally determined geometries are in good agreement. Steric strain could be ruled out as the predominant factor causing the deviation from the expected C 3 symmetry, because ab initio calculations on the model system P(NH2)3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 53 publications
6
45
0
1
Order By: Relevance
“…Specifically, Mitzel et al have shown, 19 in accord with earlier spectroscopic studies, 20 that P(NMe 2 ) 3 is inherently nontrigonal, adopting molecular C s symmetry as determined by X-ray crystallography. The distortion away from 3-fold symmetry in this case, however, is modest; the difference in bond angles about phosphorus (Δ∠N x −P−N y ) is only ca.…”
Section: Introductionmentioning
confidence: 55%
“…Specifically, Mitzel et al have shown, 19 in accord with earlier spectroscopic studies, 20 that P(NMe 2 ) 3 is inherently nontrigonal, adopting molecular C s symmetry as determined by X-ray crystallography. The distortion away from 3-fold symmetry in this case, however, is modest; the difference in bond angles about phosphorus (Δ∠N x −P−N y ) is only ca.…”
Section: Introductionmentioning
confidence: 55%
“…TheP ÀCbond lengths (between 1.675(5) and 1.683(5) )are slightly longer than observed for the P-ylide (Me 2 N) 3 P = CH 2 (1.655(6) ) [15] or the azaphosphatrane N(CH 2 CH 2 NMe) 3 P = CH 2 (1.6585 (15) ). [16] Thec rystal structure as well as the theoretically calculated molecular structure of 1·p-TolSO 3 H (Figure 3 HMPN) and the non-bonding C-C distance is even longer than in the unprotonated bisylide (3.034(4) and 3.056(4) ).…”
Section: Angewandte Chemiementioning
confidence: 76%
“…TheP N 3 framework of model tricoordinate phosphorous triamide P(NH 2 ) 3 was parameterized within C s symmetry (Figure 5a)a nd ar elaxed potential energy surface scan was conducted at the B3LYP/6-31G* level for two independent driving coordinates (bond angle q and dihedral angle f). At this level of theory,t he overall electronic energy plot (Figure 5b)d escribes am inimum for P(NH 2 ) 3 that is nearly trigonal (q = 938 8, f = 1138 8), [51] with electronic energy increasing upon planarization (f!1808 8)b ut varying only modestly for excursions of q from equilibrium. Whereas HOMO (i.e.…”
Section: Angewandte Chemiementioning
confidence: 88%